The Role of the Library in Supporting Independent Learning of Islamic Education Study Program Students at IAIN Kendari - Wulandari, Destria; Erdiyanti, Erdiyanti (Dirasah: Jurnal Pendidikan Islam, 2025)
This research aims to find out the role of the library in supporting the independent learning of PAI study program students at IAIN Kendari, to find out what services are implemented in the IAIN Kendari library, to find out how PAI study program students utilize the IAIN Kendari library for independent learning. This type of research is descriptive with a qualitative approach. The data sources used are primary data sources, namely through field studies and secondary data sources through literature studies with data collection techniques through observation, interviews and documentation. The subjects of this research were the head of the library, library staff and PAI IAIN Kendari students. Research results 1) The role of the library in supporting the independent learning of PAI students is by providing facilities in the form of a seating area equipped with tables and chairs, free WiFi, computers, AC, CCTV, bag storage racks and so on. Providing collections in the form of print and digital media. The library also procures and preserves collections of library materials so that the availability of library materials is maintained so that it can support students' independent learning process in terms of reference sources. 2) Providing services in the form of circulation services (borrowing and returning books) and IT and multimedia services used by students to use computers and access e-journals and e-books. 3) PAI students use the library as a means of carrying out independent learning with various activities carried out in the library. such as reading books to deepen knowledge, looking for books as reference material, discussing with other students and doing assignments.